Retrospective analysis of the clinical effect of spinal cord stimulation in the treatment of painful diabetic peripheral neuropathy - Cui, Dongqiang; Yang, Ming; Qiao, Yang; Gong, Zhenxing; Hu, Zeqing; Ma, Zhuang; Wu, Yang; Huo, Guitong (Frontiers in Neurology, 2025)
IntroductionThe aim of this study was to evaluate the clinical outcomes of spinal cord stimulation (SCS) in patients with painful diabetic peripheral neuropathy (PDPN).Materials and methodsNinety-two patients underwent permanent SCS implantation and completed a 6-month post-operative follow-up. The primary endpoint was patient amputation rate, and secondary endpoints included Quality of Life (QOL LC V2.0) scale, pain visual analogue scale (VAS), limb nerve conduction velocity, latency and amplitude, and vibration perception threshold (VPT).ResultsIn patients with diabetic peripheral neuropathy, QOL LC V2.0 and VAS scores were significantly improved at 6 months postoperatively compared to preoperatively (24.74%, p < 0.05; 71.87%, p < 0.05). Compared with the median and ulnar nerves of the upper extremity peripheral nerves, the conduction velocities of the common peroneal, sural, superficial peroneal and tibial nerves of the lower extremity peripheral nerves were increased (p < 0.05), the latency was significantly shortened (p < 0.05) and the amplitude was significantly increased (p < 0.05) at 6 months after surgery. Compared to the dorsum of the hand, VPTs were significantly lower in the first toe and dorsum of the foot at 6 months postoperatively compared to preoperatively (p < 0.05). The overall amputation rate was 8.69%, with 3.26% for major amputation (above the ankle) and 5.43% for minor amputation (below the ankle).ConclusionSCS can effectively relieve lower limb pain in patients with diabetic peripheral neuropathy, repair lower limb peripheral nerves, improve patients’ quality of life, and reduce amputation rate.